2009
DOI: 10.1038/ajg.2009.480
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Ionizing Radiation Exposure in a Population-Based Sample of Children With Inflammatory Bowel Diseases

Abstract: Background and Aims-The degree of diagnostic radiation exposure in children with inflammatory bowel diseases (IBD) is largely unknown. Here we describe this exposure in a population-based sample of children with IBD and determine characteristics associated with moderate radiation exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 45 publications
2
35
0
1
Order By: Relevance
“…However, moderate radiation dose was defined as one CT in a 2-year observational period, which may not be indicative of true exposure. 15 This study confirms and extends earlier work by extrapolating our data to estimate the risk at age 35 and includes a longer duration of follow-up averaging over 3 years. Our estimation of radiation exposure at age 35 further highlights the importance of perspective of a child's lifetime with regard to medical imaging and radiation exposure.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, moderate radiation dose was defined as one CT in a 2-year observational period, which may not be indicative of true exposure. 15 This study confirms and extends earlier work by extrapolating our data to estimate the risk at age 35 and includes a longer duration of follow-up averaging over 3 years. Our estimation of radiation exposure at age 35 further highlights the importance of perspective of a child's lifetime with regard to medical imaging and radiation exposure.…”
Section: Discussionsupporting
confidence: 88%
“…12 Children and adults with IBD are exposed to high radiation effective doses due to medical imaging in multiple cohorts. [13][14][15] However, no studies have evaluated medical imaging utilization and estimation of radiation exposure with extrapolation based on rate of exposure, which may identify a much larger proportion of IBD patients at high exposure to medical imaging radiation.…”
mentioning
confidence: 99%
“…Also concerning is our finding of the independent effect of psychiatric co-morbidity on undergoing abdominal imaging studies, primarily CT scans. We were not able to ascertain whether the imaging studies obtained were appropriate, but several recent studies have highlighted the high frequency of radiographic studies in CD patients [41][42][43] . Thus, it is important for treating physicians to recognize underlying psychiatric co-morbidity could be a potential risk factor for multiple radiologic studies, to practice judicious use of imaging studies and use alternate imaging modalities such as magnetic resonance imaging (MRI) studies wherever indicated and possible in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that some Crohn's patients can receive large cumulative doses (over 100 mSv) over the course of their disease, and often are examined with CT two to three times a year [39][40][41][42][43][44][45]. In one series, encompassing a 15-year period of time, the mean ionizing radiation dose was 36.1 mSv [41].…”
Section: Dose Reduction Strategies and Iterative Reconstructionmentioning
confidence: 98%